Surface Topography Steer Soft Tissue Response and Antibacterial Function at the Transmucosal Region of Titanium Implant - Safaei M.; Mohammadi H.; Beddu S.; Mozaffari H.R.; Rezaei R.; Sharifi R.; Moradpoor H.; Fallahnia N.; Ebadi M.; Jamil M.S.M.; Zain A.R.M.; Yusop M.R. (Dove Medical Press Ltd, 2025)
Metallic dental implants have been extensively used in clinical practice due to their superior mechanical properties, biocompatibility, and aesthetic outcomes. However, their integration with the surrounding soft tissue at the mucosal region remains challenging and can cause implant failure due to the peri-implant immune microenvironment. The soft tissue integration of dental implants can be ameliorated through different surface modifications. This review discussed and summarized the current knowledge of topography-mediated immune response and topography-mediated antibacterial activity in Ti dental implants which enhance soft tissue integration and their clinical performance. For example, nanopillar-like topographies such as spinules, and spikes showed effective antibacterial activity in human salivary biofilm which was due to the lethal stretching of bacterial membrane between the nanopillars. The key findings of this review were (I) cross-talk between surface nanotopography and soft tissue integration in which the surface nanotopography can guide the perpendicular orientation of collagen fibers into connective tissue which leads to the stability of soft tissue, (II) nanotubular array could shift the macrophage phenotype from pro-inflammatory (M1) to anti-inflammatory (M2) and manipulate the balance of osteogenesis/osteoclasia, and (III) surface nanotopography can provide specific sites for the loading of antibacterial agents and metallic nanoparticles of clinical interest functionalizing the implant surface. Silver-containing nanotubular topography significantly decreased the formation of fibrous encapsulation in per-implant soft tissue and showed synergistic antifungal and antibacterial properties. Although the Ti implants with surface nanotopography have shown promising in targeting soft tissue healing in vitro and in vivo through their immunomodulatory and antibacterial properties, however, long-term in vivo studies need to be conducted particularly in osteoporotic, and diabetic patients to ensure their desired performance with immunomodulatory and antibacterial properties. The optimization of product development is another challenging issue for its clinical translation, as the dental implant with surface nanotopography must endure implantation and operation inside the dental microenvironment. Finally, the sustainable release of metallic nanoparticles could be challenging to reduce cytotoxicity while augmenting the therapeutic effects. ? 2024 Safaei et al.